Edukasi Pencegahan Penyakit Diare Dan Screening Sumber Air Minum Warga Di Wilayah Kecamatan Morosi - Yunus, Reni; Hasan, Aswiro; Fauzi, Ahmad Zil (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Diarrhea cases are related to human behavior, clean water facilities, waste water disposal facilities and environmental health. The area in Morosi District is an area where the supply of clean water is still minimal and is an area close to the Morosi industrial area. Education is needed so that people can know the importance of drinking clean water to avoid diarrhea. The activity began with the distribution of questionnaires for a pre-test to measure the public's knowledge about diarrhea and the risk of contamination of drinking water sources. Then it continues with counseling or providing education, distributing leaflets and ending with a post test related to diarrhea and its prevention. Screening activities for the risk of contamination of drinking water sources for residents in Paku Village, Morosi District were carried out using the observation method using a sanitation inspection form. Educational activities regarding Diarrhea and its Prevention were carried out on September 5 2024 in Paku Village, Morosi District, Konawe Regency. Education regarding diarrhea and its prevention is very important in increasing the knowledge of the people of Paku Village, Konawe Regency. The percentage increase in public knowledge after being given education about diarrhea was 48.8%.  Based on the screening results of 10 dug wells in Paku Village, there are 7 wells that are in the Meet the Requirements (MS) category, and there are 3 other wells that are in the Not Meet the Requirements (TMS) category.